Damage analysis of rock mass coupling joints, water and microseismicity. (January 2018) - Zhou, Jingren; Wei, Jiong; Yang, Tianhong; Zhu, Wancheng; Li, Lianchong; Zhang, Penghai
Highlights: A numerical model coupling joints, water and microseismicity is proposed to simulate rock mass damage. An inversion model of rock damage based on microseismic moment tensor was proposed. The integration of microseismic data is beneficial to the prediction of rock damage development. Abstract: The behaviour of rock mass is governed by the properties of the intact rock, the joints and the water conditions. Moreover, this behaviour is also influenced by the temporal and spatial damage evolution patterns of the rock. Thus, in this study, an approach that couples joints, water and microseismicity is proposed to model rock engineering problems. Joints are used to reduce the global properties of the rock mass, water is used to reduce the local properties of the rock mass, and microseismicity are used to reduce the point properties of the rock mass. Using data from the Shirengou iron mine, the effects of water and joints on the properties of rock masses were investigated, and a representative elementary volume of rock mass was determined. Then, a coupled fluid–solid numerical model was established to simulate the evolution of rock mass damage while considering the effects of joints and water. Finally, an inversion model of rock damage based on microseismic moment tensor was proposed. A numerical simulation of rock mass damage that couples joints, water and microseismicity was performed. The rock mass damage mechanism was then analysed. Joints and water were found to significantly affect the damage zones. The rock mass damage estimate would not be accurate without considering the effects of joints and water. Thus, water was the critical factor in the studied damage pattern. Further integration of microseismic data aided in modifying the numerical results and in predicting the damage development. The proposed approach can efficiently assess rock mass damage evolution and provide a basis for rock support.